PENGARUH PENGUASAAN GERAK LURUS TERHADAP HASIL BELAJAR FISIKA SISWA MATERI HUKUM NEWTON DI KELAS X SMA NEGERI 1 PADANG BOLAK JULU - Asmaidah, Seri (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2024)
The aim of this research was to know wheater there was a significant influence between motion straight mastery and physics learning out comes in newton law subject at the tenth grade students of SMA Negeri 1 Padang Bolak Julu.The population of this research was all the tenth grade students of SMA Negeri 1 Padang Bolak Julu which include 10 classess or 205 students. The sample of this research was 42 students by using cluster technique sampling. Based on this research, it could be found that the average of straight motion mastery was 78.80 and it was categorized “good”. While the average of physics learning outcomes in newton law subject was 73.35 and it was categorized “good”. Analysis differential was conducted by using “ttest” formulation to know wheter the hyphotesis was accepted or rejected. Based on the calculation of the data, it could be found that tcount = 2.71 and ttable = 1.68, df = 42-2=40 in significant level 5%. By comparing tcount and ttable it could be seen tcount is greater than ttable (2.71>1.68) and it could be concluded that hyphotesis was accepted. It means there was a significant influence between straight motion mastery on physics learning outcome in nowton law subject at the tenth grade students of SMA Negeri 1 Padang Bolak Julu.